2013
DOI: 10.1186/1471-2350-14-72
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies MYO15A mutations as a cause of autosomal recessive nonsyndromic hearing loss in Korean families

Abstract: BackgroundThe genetic heterogeneity of hearing loss makes genetic diagnosis expensive and time consuming using available methods. Whole-exome sequencing has recently been introduced as an alternative approach to identifying causative mutations in Mendelian disorders.MethodsTo identify the hidden mutations that cause autosomal recessive nonsyndromic hearing loss (ARNSHL), we performed whole-exome sequencing of 13 unrelated Korean small families with ARNSHL who were negative for GJB2 or SLC26A4 mutations.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…We did not include in Figure or in Supp. Table S1 heterozygous variants of MYO15A when a second mutation was not identified that could explain recessively inherited deafness [Woo et al., ; Yang et al., ; Besnard et al., ; Park et al., ], except for heterozygous missense mutations of giant exon 2 for reasons discussed later in this review. Inframe insertions/deletions were categorized as “likely pathogenic.” Missense and splice‐site variants, other than canonical ±1 or 2, were also categorized as likely pathogenic only if, in addition to satisfying the aforementioned two criteria, they were predicted as damaging by the four in silico programs for evaluating missense variants and the two in silico programs for splice‐site variants that we used.…”
Section: Pathogenic Mutations Of Myo15amentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include in Figure or in Supp. Table S1 heterozygous variants of MYO15A when a second mutation was not identified that could explain recessively inherited deafness [Woo et al., ; Yang et al., ; Besnard et al., ; Park et al., ], except for heterozygous missense mutations of giant exon 2 for reasons discussed later in this review. Inframe insertions/deletions were categorized as “likely pathogenic.” Missense and splice‐site variants, other than canonical ±1 or 2, were also categorized as likely pathogenic only if, in addition to satisfying the aforementioned two criteria, they were predicted as damaging by the four in silico programs for evaluating missense variants and the two in silico programs for splice‐site variants that we used.…”
Section: Pathogenic Mutations Of Myo15amentioning
confidence: 99%
“…[Ammar‐Khodja et al., ], [Atik et al., ], [Bademci et al., ],[Bashir et al., ], [Belguith et al., ], [Brownstein et al., ], [Brownstein et al., ], [Cengiz et al., ], [Chang et al., ], [Chen et al., ], [Diaz‐Horta et al., ], [Duman et al., ], [Fattahi et al., ], [Gao et al., ], [Gu et al., ], [Imtiaz et al., ], [Kalay et al., ], [Lezirovitz et al., ], [Li et al., ], [Liburd et al., ], [Miyagawa et al., ; Miyagawa et al., ], [Miyagawa et al., ], [Moteki et al., ], [Nal et al., ], [Neveling et al., ], [Park et al., ], [Rehman et al., ], [Riahi et al., ], [Schrauwen et al., ], [Shafique et al., ], [Shahin et al., ], [Shearer et al., ], [Sloan‐Heggen et al., ], [Sloan‐Heggen et al., ], [Vona et al., ], [Vozzi et al., ], [Wang et al., ], [Woo et al., ], [Xia et al., ], [Yano et al., ], [Yang et al., ]…”
Section: Articles Cited In the Online Supporting Informationmentioning
confidence: 99%
“…; Woo et al . ). Whole‐genome sequencing is also used successfully in farm animals to gain benefits in breeding and production.…”
Section: Introductionmentioning
confidence: 97%
“…1 The clinical features of ARNSHL (hearing level, age at onset, progressiveness, associated symptoms, etc) differ according to the causative gene/genotype. [4][5][6][7] These reports suggest that MPS screening of candidate genes is an effective and useful strategy. Comprising 66 exons and 71 kbp of DNA on chromosome 17p11.2, MYO15A encodes the 3530amino acid myosin XV protein.…”
Section: Introductionmentioning
confidence: 99%